Value Creation in the Design Phase of the Architectural Projects in Iceland: Sustaining the Knowledge Clusters for Continuous Improvement - Catherine Linh Thuyvu Duong 1993- (2023)
Iceland's AEC (Architecture, Engineering, and Construction) industry is experiencing unparalleled demand and supply economics. The construction industry faces challenges such as cost overruns, fragmentation, and low repetition, leading to a lack of control and reduced performance. The industry's success depends on its capacity to add value for its stakeholders, considering both financial and non-financial value creation. This research aimed to examine the value creation in the design phase of architectural projects in Iceland. The study focuses on project management and long-term growth for continuous improvement. The study identified the current position of Icelandic AEC sectors. Project management is crucial for ensuring the longevity of buildings and the productivity of a project. A smooth quality system is essential for consistency and professionalism. A well-organised project with clear goals and communication is crucial for better productivity. The project process is divided into several stages, with structure, follow-up, and supervision essential. The company's performance is affected by various stakeholders, including designers, contractors, buyers, managers, project owners, and other influencers in decision-making, depending on the required size and level of detail. The Icelandic AEC industry has a flat hierarchy. Designer firms have a threefold structure. Most participants lack project management knowledge, but most work as project managers. Honesty and consistent people are crucial for maximizing knowledge and avoiding losing expertise. The study examines various projects in the Icelandic AEC industry. However, it has been limited, including the limited number of participants, or 14 interviewees, and the lack of observations of half of the project life cycle because the study will only examine the first part of the project life cycle, the design phase. Keywords: Value creation, architectural projects, design phase, Iceland AEC (arkitektúr, verkfræði og byggingariðnaður) á Íslandi býr við ...